2011
DOI: 10.1007/s00330-011-2183-6
|View full text |Cite
|
Sign up to set email alerts
|

Extra-mammary findings in breast MRI

Abstract: The prevalence of metastatic incidental extra-mammary findings is not negligible. Particular attention should be to incidental findings located within the lung, bone and mediastinal lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 25 publications
(30 reference statements)
4
41
0
Order By: Relevance
“…Rinaldi et al 7 reviewed 1535 breast MRI studies retrospectively and reported the prevalence of extra-mammary findings of 17.6% located most frequently in the liver (51.9%). Twenty point four percent of the incidental findings were malignant, and the positive predictive value for MRI to detect malignant lesion was high if located within the bone, lymph nodes, and lung, while it was low if located within the liver.…”
Section: Discussionmentioning
confidence: 97%
“…Rinaldi et al 7 reviewed 1535 breast MRI studies retrospectively and reported the prevalence of extra-mammary findings of 17.6% located most frequently in the liver (51.9%). Twenty point four percent of the incidental findings were malignant, and the positive predictive value for MRI to detect malignant lesion was high if located within the bone, lymph nodes, and lung, while it was low if located within the liver.…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies reported high rates of malignancy in the incidentally detected pulmonary lesions ranging from 55% to 83%, including both metastases and primary lung cancer 11,16 (Fig. 10).…”
Section: Lungmentioning
confidence: 96%
“…16 The positive predictive value (PPV) of MRI to identify a metastasis is high for incidental lesions detected in the bone (PPV, 89%), lymph nodes (PPV, 83%), and lung parenchyma (PPV, 59%) but low with those lesions discovered in the liver (PPV, 9%) or associated with pleural effusion (PPV, 6%). 11 …”
Section: Breastmentioning
confidence: 97%
See 2 more Smart Citations